Estrategias de marketing deportivo para el fortalecimiento institucional del club deportivo especializado profesional Unibolívar cantón Guaranda, provincia Bolívar para el año 2018 - Santamaría Viteri, Néstor Eduardo (2019)
The research work will be develop in the city of Guaranda, which is based on making an analysis of the actual situation of the specialized UniBolívar professional sports club, being able to determine that the same does not use strategies of sports marketing, no tools of effective marketing for appropriate management and positioning of the brand, it is for that it will make a sports marketing plan with the purpose of generating strategies based on the marketing mix( product, price, piazza, promotion) That permit to strengthen, position and promote the institutional picture as local as national. This is an organization that has like objective to guide the teaching of sport in children and young people looking for their physical development, motor, cognitive and social through the execution of integral processes and programs that motivate to the participants in the sport practice. The plan of sports marketing is a process in which born the creation of strategies, actions, techniques, tactics focused on the UniBolivar club's goal market, being this the best way to generate resources and improve aspects, applying strategies of sports marketing that will help to have success in the financial area, mercadológica, sports management and public relations for the institution. Since nowadays the soccer is considered like an economic activity and entertainment that generates and moves thousands of followers and dollars at national and global level. Descriptive terms: (sports marketing plan; strategies; marketing mix; goal market; positioning; public relations